10 hungry rabbits : counting and color concepts for the very young - Lobel, Anita (Alfred A. Knopf, 2012)
Ten rabbits are hungry for supper but Mama Rabbit has nothing to put in her soup pot, so Papa sends the little ones to the garden where they discover increasing numbers of foods in many different colors.